Cardiomyocyte cohesion is increased after ADAM17 inhibition - Shoykhet, Maria; Waschke, Jens; Yeruva, Sunil (Frontiers in Cell and Developmental Biology, 2023)
A Disintegrin And Metalloprotease (ADAM) family proteins are involved in several cardiac diseases, and some ADAMs have been associated with cardiomyopathies. ADAM17 is known to cleave desmoglein 2 (DSG2), one of the proteins involved in the pathogenesis of arrhythmogenic cardiomyopathy (AC). Desmosomal stability is impaired in AC, an inheritable genetic disease, the underlying causes of which can be mutations in genes coding for proteins of the desmosome, such as DSG2, desmoplakin (DP), plakoglobin (PG), plakophilin 2 or desmocollin 2. Stabilizing desmosomal contacts can therefore be a treatment option. In the heart of the murine AC model, Jup-/- (Jup being the gene coding for PG) mice, elevated levels of p38MAPK, an activator of ADAM17, were found. However, ADAM17 levels were unaltered in Jup-/- mice hearts. Nonetheless, inhibition of ADAM17 led to enhanced cardiomyocyte cohesion in both Jup+/+ and Jup-/- mice, and in HL-1 cardiomyocytes. Further, enhanced cohesion in HL-1 cardiomyocytes after acute inhibition of ADAM17 was paralleled by enhanced localization of DSG2 and DP at the membrane, whereas no changes in desmosomal assembly or the desmosomal complex were observed. In conclusion, acute inhibition of ADAM17 might lead to reduced cleavage of DSG2, thereby stabilizing the desmosomal adhesion, evidenced by increased DSG2 and DP localization at cell borders and eventually cardiomyocyte cohesion. We believe that similar mechanisms exist in AC.